Analisis Penggunaan Bahasa Gaul terhadap Keterampilan Komunikasi Remaja di Indonesia - Neura Shafa Salsabila; Siti Enik Mukhoiyaroh Bambang (STIKes Ibnu Sina Ajibarang, 2026)
The development of social media has made slang a dominant part of the communication of Generation Z adolescents in Indonesia. This study aims to analyze the characteristics of digital slang, its influence on adolescent communication skills, and its implications for language education. The study employed a systematic literature review with a critical interpretivism approach and reference to the PRISMA guidelines. Data were obtained from scientific articles from 2020–2026 through Google Scholar, SINTA, DOAJ, and Semantic Scholar. The results indicate that slang has ambivalent impacts. On the one hand, intensive use of slang can reduce the ability to use formal language in academic contexts. On the other hand, slang also supports the formation of social identity, group solidarity, and communication flexibility through code-switching practices. This study found that awareness of communication context is a crucial factor in determining the impact of slang use on adolescent communication competencies. Therefore, Indonesian language learning needs to develop an approach based on register awareness and digital literacy to be more relevant to the realities of Generation Z communication.